New carbon structures obtained from C70 at high pressures and high temperatures. (2017) - Marques, L.; Skorokhod, Y.; Soares, R.
Abstract: The structures of two newly discovered C70 high-pressure polymerized phases are described in a common basis. Both structures involve anti-parallel displacements of basal compact layers occurring, for each structure, along a particular unit cell axis. These displacements are crucial in the establishment of intermolecular covalent bonds and, thus, in the formation of the new phases. Pressure-temperature conditions for the synthesis of both phases are also described.